Absence of Meckel's Cave with Trigeminal Neuralgia: A Case Report - AlHatmi, Asma; Al-Qassabi, Ahmed; Raniga, Sameer Bhimjibhai; Al Ajmi, Eiman (Indian Journal of Radiology and Imaging, 2022)
Trigeminal neuralgia (TN) is a disabling painful condition along the course of the sensory distribution of the trigeminal nerve that most commonly occurs due to vascular compression or conflict at the root entry zone of the trigeminal nerve. We report a 27-year-old female patient who presented with pain and an electric shock-like sensation on the right side of her face that started three years ago. Magnetic resonance imaging of the brain was done and revealed no neurovascular conflict along the course of the trigeminal nerve. The absence of Meckel's cave with atrophy of the cisternal segment of the trigeminal nerve on the affected side was reported. The absence of Meckel's cave is an exceedingly rare cause of TN, and only a handful of reported cases in the literature suggest the association between them.
Keywords: trigeminal neuralgia; neurovascular conflict; root entry zone; Meckel's cave